Roles of autophagy-related genes in the therapeutic effects of Xuanfei Pingchuan capsules on chronic obstructive pulmonary disease based on transcriptome sequencing analysis - Zhang, Ye; Xue, Xiaoming; Meng, Lihong; Li, Dian; Qiao, Wenxiao; Wang, Jinyun; Xie, Di (Frontiers in Pharmacology, 2023)
Objective: Autophagy plays an important role in the occurrence and development of chronic obstructive pulmonary disease (COPD). We evaluated the effect of Xuanfei Pingchuan capsule (XFPC) on autophagy-related genes of COPD by a bioinformatics analysis and experimental verification. Methods: The best treatment duration was screened by CCK8 assays. HBE cells were divided into three groups: blank, CSE and XFPC. After intervened by XFPC, HBE cells were collected and sent to Shenzhen Huada Gene Company for transcriptome sequencing. Subsequently, differential expression analyses, target gene prediction, and function enrichment analyses were carried out. Expression changes were verified in HBE cells by real-time Quantitative PCR (RT-qPCR) and western blotting (WB). Results: The result of differential expression analysis displayed that 125 target genes of HBE cells were mainly related to mitogen-activated protein kinase (MKK) binding, interleukin 33 binding, 1-Pyrroline-5-carboxylate dehydrogenase activity, and the mitogen-activated protein kinase (MAPK) signal pathway. Among the target genes, the core genes related to autophagy obtained by maximum neighborhood component algorithm were CSF1, AREG, MAPK9, MAP3K7, and AKT3. RT-qPCR and WB methods were used to verify the result, it showed similar expression changes in CSF1, MAPK9, MAP3K7, and AKT3 in bronchial epithelial cells to those in the bioinformatics analysis. Conclusion: Through transcriptome sequencing and validation analysis, we predicted that CSF1, MAPK9, MAP3K7, and AKT3 may be the potential autophagy-related genes that play an important role in the pathogenesis of COPD. XFPC may regulate autophagy by down-regulating the expression of CSF1, MAPK9, MAP3K7, and AKT3, thus achieving the purpose of treating chronic obstructive pulmonary disease.